(NpROBLEMY TEORETI^ESKOJ FIZIKI (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NbARXQHTAR(B, (NwIKTOR gRIGORXEWI^s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(Nan ussr(B. (NhARXKOWSKIJ FIZIKO(B-(NTEHNI^ESKIJ IN(B-(NTs
Keywords: (NfIZIKA TEORETI^ESKAQs